Carbon information disclosure of enterprises and their value creation through market liquidity and cost of equity capital - Li Li; Yuanhua Yang; Dengli Tang (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: Drawing on asymmetric information and stakeholder theories, this paper investigates two mechanisms, namely market liquidity and cost of equity capital, by which the carbon information disclosure of enterprises can benefit their value creation. Design/methodology/approach: In this research, web crawler technology is employed to study the link between carbon information disclosure and enterprises value creation, and the carbon information data are provided by all companies listed in Chinese A-share market Findings: The results show that carbon information disclosure have significant positive influence on enterprise value creation, which is embodied in the relationship between carbon information disclosure quantity, depth and enterprise value creation, and market liquidity and cost of equity capital play partially mediating role in it, while the influence of carbon information disclosure quality and concentration on enterprise value creation are not significant in statistics. Research limitations/implications: This paper explains the influence path and mechanism between carbon information disclosure and enterprise value creation deeply, answers the question of whether carbon information disclosure affects enterprise value creation or not in China. Practical implications: This paper finds that carbon information disclosure contributes positively to enterprise value creation suggests that managers can reap more financial benefits by disclosing more carbon information and investing carbon emissions management. So, managers in the enterprises should strengthen the management of carbon information disclosure behavior. Originality/value: The paper gives a different perspective on the influence of carbon information disclosure on enterprise value creation, and suggests a new direction to understand carbon information disclosure behavior.
Keywords: 650; carbon information disclosure; market liquidity; cost of equity capital; enterprises value creation